Profile of Students’ Difficulties to Learn Geometry of Mathematics Education Study Program - Abdurrahman Abdurrahman; Nofriyandi Nofriyandi (Universitas Pahlawan Tuanku Tambusai, 2022)
This study describes mathematics education students' learning difficulties of Mathematics Education Study Program students at Riau Islamic university in Riau Province. This research is mixed-method research. The population in this study were students of Mathematics education at the Islamic University of Riau. The sampling technique uses a purposive approach by taking all active students and have studied geometry. The data collection instrument in this study used a questionnaire and interview guidelines. Data analysis used quantitative descriptive and qualitative descriptive. The analysis results show that 55.7% have difficulty remembering the concepts that have been studied (postulates, theorems, definitions, principles, procedures/operations, facts). 41% of students have difficulty understanding any geometry lecture material. 38.5% of students cannot understand the intent or problem in the given geometry problem. 54.9% of students cannot apply postulates/theorems/solve geometry problems. 41.8% of students cannot determine and sequence the steps in solving geometry problems. 36.9% of students cannot carry out a sequential, correct, and complete calculation process in solving geometry problems. There are 41% of students of the Mathematics Education Study Program at the Islamic University of Riau who are less able to be thorough and careful in solving geometry problems